Deciphering the Differential Effective and Toxic Responses of Bupleuri Radix following the Induction of Chronic Unpredictable Mild Stress and in Healthy Rats Based on Serum Metabolic Profiles - Gao, Xiaoxia; Liang, Meili; Fang, Yuan; Zhao, Fang; Tian, Junsheng; Zhang, Xiang; Qin, Xuemei (Frontiers in Pharmacology, 2018)
The petroleum ether fraction of Bupleuri Radix which is contained in the traditional Chinese medicine prescription of Xiaoyaosan (XYS) may have a therapeutic effect in depressed subjects based on the results of our previous study. It has been reported that Bupleuri Radix can cause liver toxicity following overdosing or long-term use. Therefore, this study aimed to decipher the differential effective and toxic responses of Bupleuri Radix in chronic unpredictable mild stress (CUMS) (with depression) and healthy rats based on serum metabolic profiles. Serum metabolic profiles were obtained using the UHPLC- Q Exactive Orbitrap-MS technique. Our results demonstrated that the petroleum ether fraction of Bupleuri Radix (PBR) produces an antidepressant effect through regulating glycometabolism, amino acid metabolism, sphingolipid metabolism, glycerophospholipid metabolism, and fatty acid metabolism. It also induces more severe toxic reactions in the liver or kidney in healthy rats than in CUMS rats, which exhibited a comparatively mild drug-induced toxic reaction. The altered lysine degradation, sphingolipid metabolism, glycerophospholipid metabolism, fatty acid metabolism, and bile acid metabolism could be at least partly responsible for the PBR toxic responses in healthy rats. The differential effective and toxic response of PBR in CUMS rats and healthy rats provide a new standard for the more rational and safer application of clinical drugs in the future.